ANALISIS BIBLIOMETRIX PERAN PEREMPUAN DALAM PENDIDIKAN ISLAM PADA DATABASE SCOPUS TAHUN 2012-2022 - Nadhiroh, Ulfatun Naili; Halim, Abdul; Ramadhan, Syahrul (Tarbiyatuna Kajian Pendidikan Islam, 2023)
This study aims to analyze research trends related to the role of women in Islamic education in various parts of the world which were published through the Scopus database from 2012 to 2022. This study used quantitative research methods with bibliometric analysis using R-Packages software and WebInterface Biblioshiny for analysis. and data visualization. The keywords used are 'Islamic Education', and 'Women', to generate more specific data searches with research theme categories. Based on the search results, the researcher obtained 674 scientific papers, which the authors specified using only two types of documents, namely articles and conference papers, resulting in 279 documents. The results of the study show that the theme of the role of women in Islamic education still attracts attention for research to date, even though it fluctuates every year. The most influential publication is research conducted by Noorbala A entitled "Mental Health Survey of The Iranian Adult Population in 2015". His work published in 2017 has been cited 106 times. While the most affiliation is Shahid Beheshti University of Medical Sciences with 21 publications and the most productive country with the highest number of citations is Iran with 261 citations. It is hoped that this trend-related analysis on the theme of the role of women in Islamic education can be used as a reference for further research.